Stability and reliability of the new corn hybrids in comparison to the regional control HB-83, 1998-2000. - Camargo-Buitrago, Ismael; Gordón-Mendoza, Román; Fuentes, Mario (Agronomía Mesoamericana, 2003)
A study was conducted to estimate the stability (AMMI) and the confidence or normalized response (RNI) for a white corn hybrid, assessed in a regional PCCMCA corn trial from 1998 to 2000. In this period, 100 genotypes were evaluated at 48 environments at nine Central America and the Caribbean countries. The RN1 values represents the specific genotype.s probability increase over the mean yield, specified by a control. The study allowed to identify genotypes with low environment interaction and of normalized response varying from good to average (0.6 ≥ RNI < 0.9) according with the control. The stability and the confidence degree, regarding to the regional control HB-83, was determined every year. In addition, the same analysis was performed with 12 genotypes in common at least in two year of this phase. The combined analysis indicated that 25% of genotypes showed a RNI = 0.8, these genotypes were CM 933-133, XM 7706 and XM 7708. Six of them (50%) showed standard RNI, outstanding the H-59 and CB-HS-9 with RNI values of 0.73 and 0.75, respectively; the other 25% presented low RNI, less than 0.6. The HB-83, CB-HS-11, HN- 12 and Trop E 103 were identified as hybrids with low genotype-environment interaction by the AMMI analysis. Both analysis allowed to verify that HB-83 is still a competitive and current regional control due to its high production and good stability throughout contrasting environments.